Solving the Problem of Waste Management in the Hospitality Industry- A Case Study of Chariot Hotel in Buea, South West Region (Asian Business Research, 2017)
Waste management is intended to reduce adverse effects of waste on health, the environment and challenges abound in the management and recycling of waste. This industry therefore need planning in the management and the recycling of these waste as the total rubbish or waste produced in a country is so enormous and there is also a lot of excellent work going on around many council areas or municipalities this in an effort to ensure that this is an industry to be proud of and one that will continue to secure effective, sustainable and ecologically sound waste management and recycling for many years to come. When waste is disposed of properly, you can prevent hazardous materials from contaminating the environment as well as the health of the population leaving in that area as rubbish and waste is known to cause air and water pollution and especially rotting garbage produced is also known to produce harmful gases that when it thus mix with the air it will cause breathing problems in people. The Buea Municipality which is the local government administrative unit have been left with the responsibility of overseeing the work done by this privately held organisation (HYSACAM), a local waste management company that has been contracted to manage waste in its municipality.